Meta-Analysis: The Effect of Physical Activity in Reducing Excessive Gestational Weight Gain and Gestational Diabetes Mellitus among Overweight and Obese Pregnant Women - Cahyaningrum, Hapsari; Tamtomo, Didik; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: The prevalence of overweight and obesity among women continues to increase every year. Overweight and obesity can lead to complications in pregnancy such as Excessive gestational weight gain (EGWG) and Gestational diabetes mellitus (GDM). Physical activity intervention is an option to prevent EGWG and GDM. The study aims to analyze the effects of physical activity interventions in reducing EGWG and GDM. Subjects and Method: The study used a meta-analysis study design by following PRISMA guidelines. The research question was formulated in PICO.  The population was pregnant women with a Body Mass Index (BMI) of > 25 kg/m2. The intervention used was measured physical activity. The comparison was without measured physical activity. The outcomes were EGWG and GDM. Article search was carried out through the databases such as PubMed, Cochrane Library, Scopus Database, and PEDro which was published from 2011 to 2020. The article search used the following keywords: "pregnancy" OR "pregnant woman" AND "obese" OR "overweight" AND "excessive gestational weight gain" OR "gestational weight gain" OR "weight gain" AND "gestational diabetes mellitus" OR "gestational diabetes" AND "exercise " OR "antenatal exercise" OR "physical activity". Articles that met the criteria were full-text articles with a Randomized Control Trial (RCT) study design. The assessment of the quality of the study was conducted with Cochrane Collaboration's Tool for Assessing Risk of Bias and the articles were subsequently analyzed using the Review Manager 5.4 application. Results: A total of 10 articles analyzed in this study came from Asian, European, Australian, and American countries with a total sample of 2,086. The results of the meta-analysis showed that overweight and obese pregnant women who performed measured physical activity did not experience weight changes compared to those who did not engage in physical activity (SMD= 0.03; 95% CI= 0.17 to 0.73; p=0.770).  However, overweight and obese pregnant women who do measured physical activity experience changes in fasting sugar levels compared to those who did not do measured physical activity (SMD= 0. 20; CI95%= 0.30 to 0.10; p=0.001). Conclusion: The results of this study state that physical activity interventions are effective in reducing GDM but not for EGWG in overweight and obese pregnant women. Keywords: physical activity, excessive gestational weight gain, gestational diabetes mellitus, overweight and obese pregnant women, meta-analysis. Correspondence: Hapsari Cahyaningrum. Master’s Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: hapsaricahyaningrum27@gmail.com. Mobile: 081328932469.